Dampak Penyalahgunaan Media Sosial Terhadap Kriminalitas Anak Dibawah Umur Dalam Kasus CyberBullying - Bertylla Deva Octania Tjahaja; Bintang Raja Dirgantara; Gavriela Angelita Tarigan; Muhammad Davin Putra Andrila; Nabila Piendra Al Fathiyah (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
This study seeks to examine the effects of social media misuse on juvenile delinquency, particularly in the context of cyberbullying, and to identify the factors contributing to this issue within Indonesia's digital landscape. Utilizing a normative legal research methodology, the study employs a statutory approach and a thorough literature review focusing on criminology and legal doctrines related to cyberbullying among minors.The findings indicate that the misuse of social media by children leads to pervasive and difficult-to-manage instances of cyberbullying. This behavior is driven by various motives, including the desire for anonymity, self-gratification, personal challenges, environmental influences, and a lack of awareness regarding the potential consequences of their actions.To effectively prevent and address cyberbullying among minors, enhanced law enforcement measures and comprehensive digital education are essential. This research aims to contribute to the development of policies and intervention strategies that prioritize child protection in the digital era.